2010
DOI: 10.4103/0974-777x.62866
|View full text |Cite
|
Sign up to set email alerts
|

The biology and control of leishmaniasis vectors

Abstract: Vector control remains a key component of many anti-leishmaniasis programs and probably will remain so until an effective vaccine becomes available. Technologies similar to those used for control of adult mosquitoes, specifically interior residual sprays and insecticide-treated nets, are currently at the forefront as disease control measures. This article provides a review of literature on the biology and control of sand fly vectors of leishmaniasis in the context of changing disease risks and the realities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 33 publications
0
49
1
4
Order By: Relevance
“…Topno and others 27 found that 13% of neighbors of VL cases were seropositive for leishmaniasis without showing symptoms. 15,28 In South Asia, it has been reported that living close to a previous case of VL strongly increases the risk of contracting the disease as well as acquiring a subclinical infection. 22 However, given the results and the clustering of many cases both related and unrelated, it is possible that the grouping of cases is a result of pockets of parasite activity and not the sand fly vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topno and others 27 found that 13% of neighbors of VL cases were seropositive for leishmaniasis without showing symptoms. 15,28 In South Asia, it has been reported that living close to a previous case of VL strongly increases the risk of contracting the disease as well as acquiring a subclinical infection. 22 However, given the results and the clustering of many cases both related and unrelated, it is possible that the grouping of cases is a result of pockets of parasite activity and not the sand fly vectors.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 VL is characterized by symptoms of fever, weight loss, splenomegaly, hepatomegaly, skin darkening, and anemia. 5,14 Claborn 15 reported that cured patients, those patients experiencing no symptoms, could test parasite-positive again at any point from 1 to 30 years after treatment of VL. After diagnosis and confirmation of VL, various treatment options exist.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of leishmania transmission lays on its involvement of various mammalian hosts, ranging from small rodents to big domestic animals, as reservoir hosts [57]. Human imposed environmental changes result in the modification of the micro-ecology of the parasite, the vector and the reservoir host favoring the higher transmission of leishmaniasis in areas [58]. Human activities such as deforestation, agricultural development and settlements near forested areas and domestication of animals are reasons for occurrence of both zoonotic and anthroponotic transmissions of leishmaniasis [59].…”
Section: Resultsmentioning
confidence: 99%
“…Several conventional control strategies have been developed for control of leishmaniasis spread. They are broadly classified into-(a) vector-based control methods: Methods like insecticide and residual sprays, sandfly repellents, barrier for sandfly bites through appropriate netting and clothing provide control through either elimination of vector populations or barrier for sandfly bites [10]; (b) parasite-based control methods: Treatment of leishmaniasis patients with drugs, like sodium stibogluconate, amphotericin B, miltefosine, paromomycin, etc. as a primary line of treatment [11].…”
Section: Introductionmentioning
confidence: 99%